2021
DOI: 10.1111/ijfs.14957
|View full text |Cite
|
Sign up to set email alerts
|

Effect of starch and non‐starch components on water migration, microstructure, starch retrogradation and texture of flat rice noodles made from different rice varieties

Abstract: Effects of starch and non-starch components on rice noodle quality, water migration during rehydration, texture, microstructure and starch retrogradation of dried rice flour and rice starch noodles made from five rice varieties with similar high amylose contents were examined. Rice noodle qualities depended mainly on starch properties and to a lesser extent on the presence of non-starch components. Elongation of rice flour noodles was lower than rice starch noodles due to the presence of non-starch components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 25 publications
(39 reference statements)
0
20
0
Order By: Relevance
“…Starch, as the major constituent of flours, much contributes to cooking qualities and processing performances of Chinese noodles. The different starches made from cereal, tuber and bean crops significantly differed in compositions, granular sizes, molecular structure, gelatinisation and thermal properties, which extremely affect noodle qualities (Hong et al ., 2021; Puhin et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Starch, as the major constituent of flours, much contributes to cooking qualities and processing performances of Chinese noodles. The different starches made from cereal, tuber and bean crops significantly differed in compositions, granular sizes, molecular structure, gelatinisation and thermal properties, which extremely affect noodle qualities (Hong et al ., 2021; Puhin et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Starch is the main component in wheat and consists of glucose polymers, amylose, with a linear structure of α‐1,4 linkages and amylopectin, highly branched with both α‐1,4 and α‐1,6 linkages (Shen et al ., 2021). These macropolymers are organised with a usual ratio of 1:3 in wheat, although the molecular characteristics vary in other cereal grains such as maize or rice (Ma et al ., 2020; Lubowa et al ., 2021; Puhin et al ., 2021). Over the last years, modified wheat genotypes with a higher amylose content, and consequently, resistant starch proportion have been developed (Slade et al ., 2012; Bird & Regina, 2018; Botticella et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Starch is the main component in wheat and consists of glucose polymers, amylose, with a linear structure of a-1,4 linkages and amylopectin, highly branched with both a-1,4 and a-1,6 linkages (Shen et al, 2021). These macropolymers are organised with a usual ratio of 1:3 in wheat, although the molecular characteristics vary in other cereal grains such as maize or rice (Ma et al, 2020;Lubowa et al, 2021;Puhin et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The main principle of texture analyzer is to simulate the mechanical movement such as chewing and squeezing the rice and then obtaining the indexes of textural properties in computer analysis software [6]. Previous studies have shown that textural properties can well reflect the palatability of rice [7]. Stickiness was considered to be the most important index of textural properties because it was significantly correlated with the molecular structure of amylopectin and negatively correlated with the amylose content [8].…”
Section: Introductionmentioning
confidence: 99%